PENERAPAN BUDAYA POSITIF KESEPAKATAN KELAS DI SMP - Fauziati, Fauziati; Zurita, Isesma; Lizarti, Lizarti; Yetisia, Muetia; Syofyani, Syofyani (Jurnal Dedikasi Pendidikan, 2025)
This research aims to optimize the learning environment in Indonesian language subjects at student through the implementation of a positive culture in the form of "Class Agreement". The problems faced during the previous learning process were low student participation, lack of positive interaction between students, and disorder in class which hampered the effectiveness of learning. To overcome this, teachers implement a class agreement approach by involving students in formulating mutually agreed class rules in order to create a more conducive and supportive learning atmosphere. The methods used in implementing class agreements include group discussions, drafting joint rules, and periodic evaluation of the implementation of the agreement. The results of implementing this positive culture show an increase in active student participation, the creation of more harmonious relationships between students, and the creation of a classroom environment that is more disciplined and conducive to learning. In addition, Indonesian language learning becomes more effective with increased student involvement in discussions, group assignments and other learning activities. The implementation of class agreements has proven successful in improving the quality of learning and creating a more positive learning environment